2002
DOI: 10.1161/hs0302.103735
|View full text |Cite
|
Sign up to set email alerts
|

Protective Vasomotor Effects of In Vivo Recombinant Endothelial Nitric Oxide Synthase Gene Expression in a Canine Model of Cerebral Vasospasm

Abstract: Background and Purpose-Post-subarachnoid hemorrhage (SAH) cerebral vasospasm is a potentially devastating condition whose pathogenesis involves impaired nitric oxide (NO) bioavailability. We aimed to determine whether recombinant endothelial NO synthase (eNOS) gene expression may protect vasomotor function and prevent vasospasm in a canine experimental SAH model. Methods-Recombinant adenoviral vectors (5ϫ10 9 plaque-forming units/animal) encoding genes for eNOS (AdeNOS) and ␤-galactosidase (AdLacZ) or vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 32 publications
4
72
0
Order By: Relevance
“…An animal model involving intact carotid artery was chosen as the focus for this study in the context of our ability to determine the effects of mechanical vector delivery in this tissue preparation morphologically, biochemically, and functionally, and because of our previous experience with vascular gene transfer in dogs 3,4,13,22,31 and rabbits. 19,20 Ex vivo experiments were carried out using arteries harvested from mongrel dogs.…”
Section: Animal Tissuementioning
confidence: 99%
See 4 more Smart Citations
“…An animal model involving intact carotid artery was chosen as the focus for this study in the context of our ability to determine the effects of mechanical vector delivery in this tissue preparation morphologically, biochemically, and functionally, and because of our previous experience with vascular gene transfer in dogs 3,4,13,22,31 and rabbits. 19,20 Ex vivo experiments were carried out using arteries harvested from mongrel dogs.…”
Section: Animal Tissuementioning
confidence: 99%
“…Experimental studies have demonstrated successful transfer of a variety of recombinant genes in the cardiovascular system both ex vivo and in vivo in animals and humans [1][2][3][4][5][6][7][8][9][10][11][12][13] suggesting that gene transfer technology may, in future, offer an effective therapeutic option for the spectrum of human cardiovascular diseases. [14][15][16][17][18] Most vascular gene transfer studies, to date, have utilized replication-incompetent adenovirus as a delivery vehicle for recombinant cDNA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations